MNGI-11. HIGH-GRADE AND LOW-GRADE MENINGIOMAS HARBOR DIFFERING METABOLOMIC PROFILES. (11th November 2019) - Fitzpatrick, Garrett; Rahman, Maryam; Garrett, Timothy; Kresak, Jesse
Abstract: BACKGROUND: Meningiomas are the most common primary brain tumor in adults. While the majority of meningiomas are low-grade and effectively treated by resection alone, there is a subset of tumors that have a high incidence of recurrence, metastatic potential, and morbidity. Radiation has been employed with variable success for high-grade meningiomas. No chemotherapeutic approaches have proven effective against these tumors to date. There is a need for a better understanding of this tumor type in order to provide our patients with better treatment options. OBJECTIVE: The purpose of this study is to investigate the metabolomic profile of meningiomas with a focus on comparing low- and high-grade tumors and identifying biologically significant metabolites which could correlate with overall and disease-free survival. METHODS: Ten tumor samples of each meningioma grade (WHO grades I-III) were collected from the Florida Center for Brain Tumor Research. Global metabolomic profiling by liquid chromatography mass spectrometry was performed on the frozen tumor samples. Statistical analyses were performed using the Southeast Center for Integrated Metabolomics Galaxy interface. Select metabolites which significantly differed between low-grade (WHO Grade I) and high-grade (WHO grade II-III) were identified using the Human Metabolome Database. RESULTS: Differing metabolomic profiles between low-grade and high-grade meningiomas were confirmed by multivariate analysis and demonstrated by unsupervised hierarchical clustering. Notably, lysophospholipid and sphingolipid metabolism was increased in the high-grade tumors, while FAPy-adenine, an oxidized nucleoside which may serve as a tumor marker, was decreased. Guanine was found to be consistently decreased in patients with negative outcomes. CONCLUSIONS: High-grade and low-grade meningiomas harbor different metabolomic profiles. The significance of these specific differences requires further investigation.